Nutrition-related infodemic experiences of the adults admitted to a Family Health Center in Ankara, Türkiye - Aslan, Dilek; Ayhan Başer, Duygu; Çakmakçı Kaya, Ebru; Altıntaş, Ercüment; Akdeniz, Seyla Esra (Acta Medica, 2025)
Objective: The infodemic has been a global challenge in almost all aspects of life, including nutrition-related practices. Dissemination of infodemic originating from both online and offline sources might end with risky health behaviors. Defining the case provides an opportunity to manage the infodemic. In this study, we aimed to define the nutrition-related infodemic experiences of the individuals over the age of 18 who applied to a Family Health Center in Ankara. Materials and Methods: This descriptive study investigated individuals admitted to the Family Health Center in Ankara, Türkiye, with data collected through a questionnaire developed by researchers and face-to-face interviews conducted between May and July 2023. Data analysis utilized SPSS version 23.0, employing binary logistic regression to assess associations between various variables and infodemic management. Results: The study, involving 222 participants, involved a majority of females (63.1%), married individuals (65.3%), and non-working participants (62.9%). Health-related characteristics indicated that 44.4% had diagnosed diseases, while 64.9% engaged in physical exercise meeting World Health Organization recommendations, and 25.8% reported tobacco use. Infodemic exposure was notable, with 51.8% always checking information sources, and logistic regression revealed a significantly higher infodemic experience among individuals with diagnosed diseases (OR = 3.621, 95% CI 1.244 to 10.545, p = 0.018). Conclusion: In summary, our study suggests the presence of an infodemic related to nutrition behavior within healthcare environments. Based on these findings, we advocate for proactive measures and structured initiatives to address infodemic challenges in healthcare settings. Moreover, we encourage future investigations to delve deeper into the underlying dynamics of this phenomenon.